Penerapan Metode SAW (Simple Additive Weighting) untuk Pemilihan Kain Terbaik - Salahudin Robo; Ayu Rahmawati Rumalean; Trisno Trisno; Rahmat Surya Baskara; Sahlan M Saleh (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The many types of fabrics at the Modiss Textile store provide choices according to consumer tastes. However, purchases at this fabric store are still processed manually and not computerized. In selecting fabrics, consumers only focus on color and price tags. This research was conducted at the Modiss Textile & Taylor store, which is a store engaged in fashion retail. In completing this research, several research methods were used to collect data, namely interviews, observations and the application of the saw method. Based on the results of collecting data on fabric selection, criteria are needed in making decisions. The application of the SAW (Simple Additive Weighting) method has the greatest value from the calculation of the value of Vi obtained by alternative fabrics, namely Spandex Fabric with a value of 0.875, Brukat Lace Fabric with a value of 0.8, Italian Wool fabric with a value of 0.775. The purpose of this research is to create a decision support system that can be used by Modiss Textile & Taylor's customers in selecting fabrics that match the criteria provided by the store, namely fabric type, color, price, texture, and quality. Then the desired result is a decision support system that can be used by customers or consumers to choose fabrics at the Modiss Textile & Taylor store